Primary hypotheses of global areas of endemism based on the distribution of Tabanomorpha (Diptera, Brachycera) - Klassa, Bruna; Santos, Charles Morphy D. (Zootaxa, 2018)
Areas of endemism, or worthy for conservation, are mainly determined based on large data sets of vertebrates and plants. Herein, we investigated the global distribution at the species-level of the infraorder Tabanomorpha (Diptera, Brachycera), identifying areas of endemism for the group. We performed an endemicity analysis through a grid-based method—NDM/VNDM—using 1,385 species (6,392 geographical records) of Tabanomorpha. The grid size of the analysis was 7º and we applied the loose consensus rule (31%) in the recovered areas. Our results revealed 479 total areas of endemism and 18 consensus areas: the whole Neotropical region, six areas in the Nearctic region, two in the Palearctic region, and three areas in each the Oriental, Australian, and African regions. There are parallels among our results and previously proposed bioregionalisation schemes established by other taxa, showing a way forward for using insects to determine global patterns of endemism.